A novel polypeptide encoded by circSPIRE1 promotes prostate cancer proliferation and migration by restraining the ubiquitin-dependent degradation of LRP5 - Jintao Hu; Juanyi Shi; Junjie Wang; Yunfei Xiao; Degeng Kong; Mingchao Gao; Tianlong Luo; Shizhong Xu; Zhihan Yuan; Xinyi Ma; Xueseng Dong; Jingang Huang; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Circular RNAs (circRNAs) are increasingly implicated in tumor progression, but the roles of protein-coding circRNAs remain largely unexplored. This study characterizes a novel circRNA-encoded protein, rtSPIRE1, and investigates its mechanistic role in prostate cancer proliferation and migration, as well as its diagnostic and therapeutic potential. Methods RNA microarray identified circSPIRE1 in prostate cancer tissues. The translation of rtSPIRE1 was confirmed by polysome profiling analysis, Western blotting, and mass spectrometry. Expression levels of circSPIRE1 and rtSPIRE1 were analyzed via qPCR, FISH, and immunohistochemistry. Gain- and loss-of-function assays were performed to evaluate their effects on cell proliferation and migration. Mechanistic studies were conducted using RNA pulldown, RIP, co-immunoprecipitation, and molecular docking. Results We identified rtSPIRE1, a novel protein encoded by circSPIRE1 through rolling circle translation, whose expression is regulated by hnRNPA1-mediated symmetric dimethylation. Both circSPIRE1 and rtSPIRE1 were significantly upregulated in prostate cancer tissues and cell lines, with higher expression levels correlating with worse prognosis. Mechanistically, rtSPIRE1 stabilized LRP5 by inhibiting its ubiquitination and degradation, leading to sustained activation of the PI3K/AKT signaling pathway, which ultimately promotes prostate cancer cell proliferation and migration. Conclusions Our findings identify rtSPIRE1 as a critical oncogenic protein encoded by circSPIRE1 through rolling circle translation, with its expression regulated by hnRNPA1-mediated symmetric dimethylation. Mechanistically, rtSPIRE1 promotes proliferation and migration by stabilizing LRP5 and activating the PI3K/AKT signaling pathway. Together, circSPIRE1 and rtSPIRE1 represent promising diagnostic biomarkers and therapeutic targets for prostate cancer.